Chapter Valorization of Natural Antioxidants for Nutritional and Health Applications - Pedro, Ferreira-Santos (InTechOpen, 2021)
The significant increase in the world population age, 47 years in 1950 to 73 years in 2020, resulted in an increase in aging related diseases as well as in degenerative diseases. In consequence, researchers have been focusing in the development of new therapies, with a particular emphasis on the use of compounds with antioxidant properties, namely phytochemicals, such as polyphenols and carotenoids. Several in vitro and in vivo studies have demonstrated the phytochemicals antioxidant capacity. Their use is broad, as they can be part of food supplements, medicine and cosmetics. The health benefit of antioxidant phytochemicals is an indisputable question. Phytochemical properties are highly influenced by the natural matrix as well as by extraction process, which have a key role. There are several extraction methods that can be applied depending on the chemical properties of the bioactive compounds. There is a wide range of solvents with different polarities, which allows a selective extraction of the desired target family of compounds. Greener technologies have the advantage to reduce extraction time and solvent quantity in comparison to the most traditional methods. This chapter will focus on the different green extraction strategies related to the recovery of antioxidant bioactive compounds from natural sources, their nutritional and health potential.